Tunable electromagnetic damper with synthetic impedance and self-powered functions. (October 2021) - Li, Jin-Yang; Zhu, Songye
Highlights: A novel H-bridge circuit based electromagnetic damper (HB-EMD) is proposed. HB-EMD can emulate behavior of various conventional dampers with self-powered feature. A single HB-EMD can offer versatile behavior by altering its control algorithm coding only. Feasibility of HB-EMD is validated analytically, numerically, and experimentally. Scalability discussion suggests enlargement of HB-EMD is practical. Abstract: Electromagnetic dampers (EMDs), which are regarded as an emerging type of dampers, have recently drawn increasing research interests in structural vibration control due to their unique advantages over conventional damper types. Although advanced synthetic impedance and energy harvesting functions of EMDs have been separately investigated, their integration has not been explored to the best of the authors' knowledge. The major obstacle herein is that the former versatile damper behavior is normally realized by consuming input energy, whereas the latter can only provide pure damping behavior comparable to passive viscous dampers while producing output energy. To fill this research gap, this study proposes a novel H-bridge circuit based EMD (HB-EMD), which allows bidirectional power flow between the EMD and the energy pool, and enables the realization of versatile damper behavior with the salient self-powered feature. The system design, working mechanism, synthetic impedance technique, power analyses, and emulation of various conventional dampers by using HB-EMD, are analytically, numerically, and experimentally examined. Scalability issues of HB-EMD are also discussed to shed light on future large-scale applications.